2014
DOI: 10.1111/vco.12082
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of feline lymphoma using a 12‐week, maintenance‐free combination chemotherapy protocol in 26 cats

Abstract: The aim of this prospective clinical trial was to investigate the efficacy and toxicity of a short-term, maintenance-free chemotherapy protocol in feline lymphoma. Twenty-six cats with confirmed diagnosis of high-/intermediate-grade lymphoma were treated with a 12-week protocol consisting of cyclic administration of L-asparaginase, vincristine, cyclophosphamide, doxorubicin and prednisolone. Complete (CR) and partial remission (PR) rates were 46 and 27%, respectively. Median duration of first CR was 394 days c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 29 publications
5
46
1
1
Order By: Relevance
“…These survival times are generally longer in duration because response to treatment and achieving complete remission has been shown to correlate with longer survival times for this disease. Similarly, the DFI of the current study (357 days) was found to be similar to the previously reported remission durations ranging from 126 to 394 days . The reported DFI in this study is admittedly an overestimation considering that some of the cases were in a more advanced stage of disease and therefore would have gone into remission later during the course of treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These survival times are generally longer in duration because response to treatment and achieving complete remission has been shown to correlate with longer survival times for this disease. Similarly, the DFI of the current study (357 days) was found to be similar to the previously reported remission durations ranging from 126 to 394 days . The reported DFI in this study is admittedly an overestimation considering that some of the cases were in a more advanced stage of disease and therefore would have gone into remission later during the course of treatment.…”
Section: Discussionsupporting
confidence: 93%
“…The median overall survival times for these studies range from 78 to 280 days, all of which are lower than the observed survival time of 417 days in this study. This survival time is perhaps more comparable to the MSTs of cats that achieved complete remission in recent studies, which have been reported as being 290 to 654 days . These survival times are generally longer in duration because response to treatment and achieving complete remission has been shown to correlate with longer survival times for this disease.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The alimentary tract is now the most frequently diagnosed primary site for LSA. The incidence of LSA in other sites, which are more commonly affected by feline leukemia virus‐related cancer, is decreasing . Feline gastrointestinal (GI) LSA is histologically subtyped according to the World Health Organization (WHO) classification system.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in dogs, in which multicentric LSA predominates and is overwhelmingly responsive to chemotherapy, the response to multiagent chemotherapy in cats with feline GI large‐cell LSA is less predictable, with overall response rates ranging from 30% to 75% . Response durability also tends to be less favorable, with reported median survival times (MST) of 3 to 6 months . However, MST tends to be closely linked to response to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%